Design of wideband AMC integrated monopole antenna with enhanced radiation performances for off‐body systems. Issue 5 (17th December 2020) - Hazarika, Bidisha; Basu, Banani; Nandi, Arnab
Abstract: A low‐profile, wideband, high gain artificial magnetic conductor (AMC) integrated monopole antenna is proposed in the letter. The bowl‐shaped stair styled monopole with defected round type partial ground is integrated with the AMC containing 2 × 2 unit‐cells to broaden the impedance bandwidth by 92.7%/66.2%/53.9% at the three resonating notches at 6/8.4/10.3 GHz respectively. The AMC has covered ±90° reflection phase bandwidth from 6.20 to 7.44 GHz (18.56%). The planar AMC proffers mu‐negative (MNG) properties and polarization independent behavior. Introduction of AMC beneath the monopole achieves wideband from 5.39 to 10.95 GHz. The AMC integrated monopole provides peak gain up to 10.6 dB which is 66.8% better than that of the only monopole. The integrated antenna offers low‐profile features with unidirectional radiation behavior, up to 18.6 dB front to back ratio (FBR) and >90% efficiency. The proposed design reduces 1‐g averaged Specific Absorption Rate (SAR) at 1 mm distance up to 96.6% at the respective bands.